Early social communication development in infants with autism spectrum disorder. Issue 6 (17th November 2021) - Bradshaw, Jessica; McCracken, Courtney; Pileggi, Moira; Brane, Natalie; Delehanty, Abigail; Day, Taylor; Federico, Alexis; Klaiman, Cheryl; Saulnier, Celine; Klin, Ami; Wetherby, Amy
Abstract: Social‐communication differences are a robust and defining feature of autism spectrum disorder (ASD) but identifying early points of divergence in infancy has been a challenge. The current study examines social communication in 9‐ to 12‐month‐old infants who develop ASD ( N  = 30; 23% female; 70% white) compared to typically developing (TD) infants ( N  = 94, 38% female; 88% white). Results demonstrate that infants later diagnosed with ASD were already exhibiting fewer social‐communication skills using eye gaze, facial expression, gestures, and sounds at 9 months (effect size: 0.42–0.89). Moreover, three unique patterns of change across distinct social‐communication skills were observed within the ASD group. This study documents that observable social‐communication differences for infants with ASD are unfolding by 9 months, pointing to a critical window for targeted intervention.